2005
DOI: 10.1158/0008-5472.can-04-4281
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Genetic Signature of Activated Signal Transducer and Activator of Transcription 3 in Human Tumors

Abstract: Signal transducer and activator of transcription 3 (STAT3) is a transcription factor that is activated in diverse human tumors and may play a direct role in malignant transformation. However, the full complement of target genes that STAT3 regulates to promote oncogenesis is not known. We created a system to express a constitutively active form of STAT3, STAT3-C, in mouse fibroblasts and used it to identify STAT3 targets. We showed that a subset of these targets, which include transcription factors regulating c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
178
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 177 publications
(182 citation statements)
references
References 35 publications
4
178
0
Order By: Relevance
“…This suggested that STAT1 may also be regulating BCL6. Additionally, it has been shown that expression of activated STAT3 in fibroblasts leads to upregulation of BCL6 expression (Alvarez et al, 2005), raising the possibility that STAT3 may also regulate BCL6 expression. In addition to activating STAT5, IL-2 also can activate STAT1 and STAT3 (Frank et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that STAT1 may also be regulating BCL6. Additionally, it has been shown that expression of activated STAT3 in fibroblasts leads to upregulation of BCL6 expression (Alvarez et al, 2005), raising the possibility that STAT3 may also regulate BCL6 expression. In addition to activating STAT5, IL-2 also can activate STAT1 and STAT3 (Frank et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…At the present time, the STAT3 transcriptional response is only partially understood, with a large number of STAT3 transcriptional targets being identified just in the last few months. 52,53 Further study of these STAT3 targets in the context of differentiating myeloid progenitors might be required before the full implication of STAT3 phosphorylation in MMM progenitors is completely appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…STAT signaling is critical for normal cellular processes such as embryonic development, organogenesis and organ function, innate and adaptive immune function, regulation of cell differentiation, growth, and apoptosis [122][123][124][125][126][127]. In normal cells, STAT3 protein activation is strictly controlled to prevent unscheduled gene regulation, while constitutive activation of STAT3 has been detected in a wide number of human cancer cell lines and primary tumors, such as 50% of HCC, leukemias, lymphomas, multiple myelomas, prostate, gastric, breast, lung, and head and neck cancer [128][129][130][131][132][133][134].…”
Section: Activation Of Stat3mentioning
confidence: 99%